Audiologic changes after pinna augmentation - Amin, Kavit; Hone, Robert; Kanegaonkar, Rahul (Ear, nose, & throat journal, 2016)
No studies to date have objectively assessed whether pinna morphology affects sound intensity detected within the external auditory canal (EAC). Commonly performed procedures on the EAC are carried out for acquired and congenital pathology, together with correction of ear deformities. Our aim was to use an experimental model to identify whether a relationship exists between pinna shape and its subsequent effect on the hearing subject. An anatomically accurate and life-size model made of rubber composite was used for this study. Serial sections (small wedge, defect open; small wedge, defect closed; large wedge, defect open; large wedge, defect closed [equivalent to a protruding ear]; and pinnectomy) were undertaken, and the sound intensity changes assessed at the junction between the EAC and middle ear (tympanic membrane position) using an AURICAL Plus (Otometrics; Taastrup, Denmark) sound processor. A statistically significant loss was demonstrated for wedge-excised models, which was greatest at 180° azimuth. This loss was significantly reduced when the wedge defects were closed. A statistically significant improvement was demonstrated in the protruding ("bat") ear model compared with the normal ear at 0° azimuth. In this model, gain in sound intensity is adversely affected by pinna wedge resection. Because this change may be increased in those with protruding ears, this factor is important to consider for all cosmetic and noncosmetic operations to the pinna, and it supports the notion that the pinna is not a simple funnel.